PERAN ENGAGING LEADERSHIP TERHADAP KOMITMEN ORGANISASIONAL DALAM PROXIMAL WITHDRAWAL STATES - Kentami, Maria Regina Tinon Dyah; Rostiana, Rostiana (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2020)
Preserving competent employees is still a primary challenge for the organization today. Every company needs to make efforts to retain the employees they have. PT.X is one of the companies operating in the education sector that needs to anticipate future turnovers. This study aims to investigate the role of engaging leadership toward organizational commitment in the Proximal Withdrawal States (PWS) at PT.X. Researchers hope that by great engaging leadership, the organizational commitment will improve so that the probability of turnover will decrease. The study was administered on 295 employees at PT.X, who is a permanent employee and had worked for more than one year. This research belongs to non-experimental quantitative research. A simple regression model was conducted to process the data of this study. The results showed that engaging leadership had a significant role of 16.8% toward organizational commitment. However, based on the situation description, engaging leadership only plays a significant role in the "reluctant stayers," "reluctant leavers," and "enthusiastic stayers" situation. In the "reluctant stayers" situation, engaging leadership accounts for 12.1%. In the "reluctant leavers" situation, a significant role of 62.7% was found, and 8.4% in the "enthusiastic stayers" situation. Furthermore, it is revealed that engaging leadership only plays a significant role toward the continual and normative commitment dimensions in the "reluctant stayers" situation. Meanwhile, in the "reluctant leavers" and "enthusiastic stayers" situation, engaging leadership only plays a significant role in the affective and normative commitment dimensions.Memperoleh karyawan yang kompeten saat ini masih menjadi tantangan utama bagi organisasi. Setiap perusahaan perlu melakukan upaya untuk mempertahankan karyawan yang dimilikinya saat ini. PT. X menjadi salah satu perusahaan yang bergerak di bidang Pendidikan yang perlu melakukan antisipasi terjadinya turnover di masa depan. Penelitian ini bertujuan untuk melihat peran engaging leadership terhadap komitmen organisasi dalam situasi Proximal Withdrawal States (PWS) pada PT. X. Peneliti berharap dengan engaging leadership yang baik, maka komitmen organisasi akan meningkat sehingga peluang terjadinya turnover akan munurun. Penelitian dilakukan pada 295 karyawan yang bekerja di PT. X dengan kriteria sebagai pegawai tetap dan sudah bekerja lebih dari satu tahun. Penelitian ini termasuk ke dalam penelitian kuantitatif non eksperimental. Pengolahan data dilakukan dengan model regresi sederhana. Hasil penelitian menunjukan bahwa engaging leadership berperan signifikan sebesar 16,8% terhadap komitmen organisasi. Namun pada gambaran situasi, engaging leadership hanya berperan signifikan pada situasi reluctan stayers, reluctant leavers dan enthusiastic stayers. Pada situasi reluctant stayers, engaging leadership berperan sebesar 12,1%. Pada situasi reluctant leavers berperan signifikan sebesar 62,7% dan 8,4% pada situasi enthusiastic stayers. Lebih detil lagi dijabarkan bahwa engaging leadership hanya berperan signifikan terhadap dimensi  komitmen kontinual dan normatif dalam situasi reluctant stayers. Sementara itu pada situasi reluctant leavers dan enthusiastic stayers, engaging leadership hanya berperan signifikan pada dimensi komitmen afektif dan normatif.